Development of hardening treatments for 58Ni39Ti-3Hf alloy system as compared to baseline 60NiTi. (October 2021) - Khanlari, Khashayar; Shi, Qi; Li, Kefeng; Yan, Xingchen; Cao, Peng; Wang, Xiaojian; Liu, Xin
Abstract: 58Ni39Ti-3Hf alloy system has been proposed as an alternative for superelastic 60NiTi used in load-bearing applications. This research was focused on the development of heat treatment procedures leading to 58Ni39Ti-3Hf parts with maximum possible hardness values. Meanwhile, the relations existing between the heat treatment – microstructure – hardness of 58Ni39Ti-3Hf as compared to baseline 60NiTi were also investigated. These were done by applying the solution and consequent aging treatments on the studied alloy systems at different temperatures and for different times. The microstructure and hardness of the treated samples were, in the next step, analyzed by applying electron probe micro-analyzer (EPMA), energy dispersive X-ray spectrometer (EDS), X-ray diffraction (XRD), transmission electron microscopy (TEM) and macro hardness testing techniques. It was understood that applying solution treatments at temperatures above about 1000 °C resulted in the relatively full dissolution of Ni-rich phases such as Ni3 Ti and Ni3 Ti2, existing in the microstructure of as-received parts, in the NiTi matrix of 60NiTi. On the other hand, for 58Ni39Ti-3Hf, temperatures above about 900 °C appeared to be adequate to solve these Ni-rich phases in the NiTi matrix. Applying aging treatments had either no significant effect on the hardness of solution treated 60NiTi samples (~58 HRC) or reduced their values; after coarsening of Ni4 Ti3 particles formed in NiTi matrix and their transformation to Ni3 Ti and Ni3 Ti2 phases. On the other hand, some of the applied aging treatments could increase the hardness values of the solution treated 58Ni39Ti-3Hf alloys (~54 HRC). The maximum value of hardness (~59 HRC) for the aged 58Ni39Ti-3Hf parts was obtained for the ones treated at 500 °C for just 0.25 h. This level of obtained hardness is comparable to that of solution treated 60NiTi. A delayed precipitation of Ni3 Ti and/or Ni3 Ti2 phases was noted in aged 58Ni39Ti-3Hf alloy system as compared to 60NiTi. Highlights: The difference amongst the solvus temperature of 58Ni39Ti-3Hf as compared to 60NiTi was understood. The peak hardness for 58Ni39Ti-3Hf (~59 HRC) was obtained by aging the solution treated samples at 500 °C for 0.25 h. Relations existing between the heat treatment-microstructure-hardness of 58Ni39Ti-3Hf as compared to 60NiTi were defined.